2015
DOI: 10.1159/000368501
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated Interferon (Alone or With Ribavirin) for Chronic Hepatitis C in Haemodialysis Population

Abstract: Background/Aims: Hepatitis C virus infection remains prevalent among patients undergoing long-term haemodialysis and has a detrimental impact on survival in this population. Antiviral therapy for chronic hepatitis C in haemodialysis patients is still a challenge to clinicians. The aim of the current study is to evaluate the efficacy and safety of therapy with pegylated interferon, alone or combined with ribavirin, for chronic hepatitis C among patients undergoing long-term hemodialysis. Methods: We conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…Sustained virologic response (SVR) rates with peg‐IFN monotherapy (approximately 40%) in HCV‐infected patients were slightly greater than those with conventional interferon therapy (approximately 30%). The addition of ribavirin did not result in better SVR rates than those associated with the use of peg‐IFN alone . However, interferon and ribavirin are associated with significant toxicity, including influenza‐like symptoms, anaemia, and depression .…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Sustained virologic response (SVR) rates with peg‐IFN monotherapy (approximately 40%) in HCV‐infected patients were slightly greater than those with conventional interferon therapy (approximately 30%). The addition of ribavirin did not result in better SVR rates than those associated with the use of peg‐IFN alone . However, interferon and ribavirin are associated with significant toxicity, including influenza‐like symptoms, anaemia, and depression .…”
mentioning
confidence: 86%
“…Earlier studies suggested that antiviral therapy for chronic hepatitis C with PEGylated interferon (peg‐IFN) alone or with ribavirin (rib) was less effective and accompanied by numerous side‐effects that led to increased safety concerns . Sustained virologic response (SVR) rates with peg‐IFN monotherapy (approximately 40%) in HCV‐infected patients were slightly greater than those with conventional interferon therapy (approximately 30%).…”
mentioning
confidence: 99%
“…At the beginning of the century, a combination of pegylated interferon and ribavirin became the standard treatment for HCV [11,12,13]. However, adverse effects of treatment with interferon and ribavirin in patients with chronic kidney disease (CKD) and the resulting poor outcomes [13] have greatly restricted widespread use of this combination.…”
Section: Introductionmentioning
confidence: 99%
“…Few Serbian hemodialysis patients were treated with these medications, with modest results, so the majority remains treatment naïve. Interferon based therapy is neither effective (a SVR rate of 40-58%) nor safe (a 26.9% withdrawal rate due to side-effects) in patients with end stage renal disease (ESRD) [17,18]. Sofosbuvir / ledipasvir, grazoprevir / elbasvir and 3D regimen were approved for clinical use in Serbia during 2016/17.…”
Section: Discussionmentioning
confidence: 99%